Morphological characteristics of young female artistic gymnasts from the Czech Republic - Kutac, P.; Jurkova, S.; Farana, R. (Science of Gymnastics Journal, 2019)
The aim of the study is to analyse the somatic parameters of artistic gymnasts in the pupil competition category and to compare them with the values of the general population in the corresponding age group. The study included 16 female gymnasts in the pupil category and 652 girls in the same age group, which formed the control group. Body height was measured using a stadiometer InBody BSM 370, body mass and body composition by BIA analyser InBody 770 (Biospace, South Korea). The monitored values of each gymnast we compared with the mean values of the control group at the corresponding age separately, using the normalisation index (Ni). The results of the study show that the gymnasts in the youngest competition category already differ in basic anthropometric parameters from the general population. Since the age of nine, the gymnasts have a lower body height (except for one person) and lower body weight than the girls in the general population. The body height and body mass values are below average or highly below average in nine gymnasts (56.3%). The high volume of specific physical activity of the gymnasts, included in their training, affects their body composition parameters. The gymnasts have lower body fat (%) and visceral fat (cm2), their values are below average to highly below average, and higher skeletal muscle mass (%), with values above average or highly above average.